2021
DOI: 10.1109/access.2021.3064226
|View full text |Cite
|
Sign up to set email alerts
|

Post-Adaptation Effects in a Motor Imagery Brain-Computer Interface Online Coadaptive Paradigm

Abstract: Online coadaptive training has been successfully employed to enable people to control motor imagery (MI)-based brain-computer interfaces (BCIs), allowing to completely skip the lengthy and demotivating open-loop calibration stage traditionally applied before closed-loop control. However, practical reasons may often dictate to eventually switch off decoder adaptation and proceed with BCI control under a fixed BCI model, a situation that remains rather unexplored. This work studies the existence and magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
(173 reference statements)
0
7
0
Order By: Relevance
“…Yet, they only partially showed that online decoder adaptation supports BCI skill acquisition as just selected subjects were discussed in terms of their final EEG patterns. Nevertheless, other studies found that online decoder adaptation did not support subject learning even if BCI performance improved ( 44 , 45 ). Intermittent decoder recalibration using data from previous sessions also promoted subject learning ( 13 , 15 , 29 ), although they required longer number of training sessions than the approaches reported in this work.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Yet, they only partially showed that online decoder adaptation supports BCI skill acquisition as just selected subjects were discussed in terms of their final EEG patterns. Nevertheless, other studies found that online decoder adaptation did not support subject learning even if BCI performance improved ( 44 , 45 ). Intermittent decoder recalibration using data from previous sessions also promoted subject learning ( 13 , 15 , 29 ), although they required longer number of training sessions than the approaches reported in this work.…”
Section: Discussionmentioning
confidence: 98%
“…Supervised approaches that use labeled samples when recalibrating the BCI decoder are popular ( 16 , 18 , 41 , 43 , 45–47 ), as ML theory predicts that they would lead to better model fitting and performance—a result verified in a cross-over BCI study comparing supervised vs. fully unsupervised approaches for online decoder adaptation ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various research have demonstrated the positive impact of adding MI EEG data from periods in which users received sensory feedback, to calibrate the BCI [19]. Is the BCI's output completely correlated to the user's intention by using this strategy?…”
Section: Introductionmentioning
confidence: 99%
“…These metrics should also inform earlier stage BCI development before end-user evaluation [139,140]. Further factors should be considered when designing the BCI paradigm, for instance, the design of tasks, feedback, instructions, and signal processing [86,[141][142][143]. Performance may improve via engaging task design (e.g.…”
Section: Organizer: Sebastian Halder (University Of Essex)mentioning
confidence: 99%